Pengaruh Komitmen Organisasi Dan Kompensasi Terhadap Kinerja Karyawan Dengan Kepuasan Kerja Sebagai Variabel Intervening Pada Lapak TBS Kelapa Sawit CV. Mitra Makmur Di Mesuji - Jimi Hidayat; Sugeng; Febriyanto (Universitas Muhammadiyah Metro, 2025)
This research was motivated by the researcher's curiosity regarding how Organizational Commitment, Compensation, and Job Satisfaction can have a significant influence on Employee Performance at the TBS Kelapa Sawit CV. Makmur Partners. The aim that researchers want to achieve in this research is to find out whether organizational commitment and compensation influence employee performance and to find out whether organizational commitment and compensation influence employee performance through job satisfaction. The method used in this research is a quantitative method, in the data collection process the researcher used a questionnaire distribution technique to 30 respondents. The data analysis technique uses Requirements Analysis Test and path analysis test. The research results show that organizational commitment has a direct effect on employee performance, compensation has a direct effect on employee performance, organizational commitment has a direct effect on employee performance through job satisfaction ( ). Compensation influences employee performance through job satisfaction, and job satisfaction influences employee performance ( ).